Cavity-Mediated Collective Emission from Few Emitters in a Diamond Membrane - Maximilian Pallmann; Kerim Köster; Yuan Zhang; Julia Heupel; Timon Eichhorn; Cyril Popov; Klaus Mølmer; David Hunger (Physical Review X)
When an ensemble of quantum emitters couples to a common radiation field, their polarizations can synchronize and a collective emission termed superfluorescence can occur. Entering this regime in a free-space setting requires a large number of emitters with a high spatial density as well as coherent optical transitions with small inhomogeneity. Here, we show that, by coupling nitrogen-vacancy centers in a diamond membrane to a high-finesse microcavity, also few, incoherent, inhomogeneous, and spatially separated emitters—as are typical for solid state systems—can enter the regime of collective emission. We observe a superlinear power dependence of the emission rate as a hallmark of collective emission. Furthermore, we find simultaneous photon bunching and antibunching on different timescales in the second-order autocorrelation function, revealing cavity-induced interference in the quantized emission from about 15 emitters. We develop theoretical models for mesoscopic emitter numbers to analyze the behavior in the Dicke state basis and find that the population of collective states together with cavity enhancement and filtering can explain the observations. Such a system has prospects for the generation of multiphoton quantum states, the preparation of entanglement in few-emitter systems, and enhancement of signals in quantum sensing.